Integrated path DIAL for standoff detection of acetone vapors under topographic target condition. (November 2021) - Jindal, M.K; Veerabuthiran, S.; Mainuddin,; Razdan, A.K.
Highlights: Tunable IR DIAL was used for remote detection of chemical vapors. The system was calibrated with the diesel. Acetone vapors were detected in closed and open chamber conditions. The dynamics of acetone column content concentration analyzed. The effect of interfering molecules on lidar signal is estimated. Abstract: A mid infrared tunable Differential Absorption Lidar (DIAL) operating in the spectral region of 3000–3450 nm has been developed and its performance has been evaluated by measuring the vapors of diesel and acetone. Diesel, one of the hydrocarbon products has been used for calibration of the DIAL wavelengths. Transmittance spectrum of diesel has been measured in 3360–3390 nm wavelength band using this system. Further, these absorption lines have been validated using Fourier Transform Infrared (FTIR) measured spectra. Acetone, one of the precursors employed in the manufacturing of Improvised Explosive Devices (IED), is used in field experiments. Firstly, the transmittance spectra of acetone vapors in the glass cell is recorded in the spectral band 3250–3365 nm using this setup. Further, the spectra have been compared with the data reported by NIST. Based on the analysis, the wavelengths at 3254 nm and 3362 nm have been chosen as offline and online wavelengths respectively. For open field experiments, a test chamber made of transparent PMMA (polymethyl methacrylate) material with openable windows on both sides placed at standoff distance of 100 m has been used. Standoff measurements have been carried out by keeping the chamber closed as well as open conditions. The average column content of acetone vapors has been measured for closed and open chamber conditions. During open chamber condition, the maximum concentration of about 13180 ppm.m has been measured. The average minimum concentration of about 30 ppm.m was observed during final dispersion stages. The influence of the atmospheric interfering molecules in the measurement wavelengths have also been analyzed and quantified their contribution in the return signals. The total contribution of these molecules in the return signal is about 0.3% at online wavelength whereas this is about 0.13% at offline wavelength.